Toward "strong" green nanocomposites: polyvinyl alcohol reinforced with extremely oriented cellulose whiskers - Jalal Uddin, Ahmed; Araki, Jun; Gotoh, Yasuo (Biomacromolecules, 2011)
To exploit the maximum potential of cellulose whiskers (CWs), we report here for the first time the successful fabrication of nanocomposites reinforced with highly oriented CWs in a polymer matrix. The nanocomposites were prepared using polyvinyl alcohol (PVA) and a colloidal suspension of cotton-derived CWs. The macroscopically homogeneous PVA-CW suspensions were extruded into cold methanol to form gel fibers followed by a hot drawing. Compared to the neat PVA fiber, the as-spun fiber containing a small amount of CWs (5 wt % of solid PVA) showed higher drawability, leading to an extremely high orientation of CWs with the matrix PVA. The stress-transfer mechanism, a prime determining factor for high mechanical properties of nanocomposites, was studied by X-ray diffraction. The stress on the incorporated CWs was monitored by applying an in situ nondestructive load to the composite fibers. The applied stress to the whole sample was found to be effectively transferred to the CWs inside the composites, suggesting strong interfacial bonding between the filler and the matrix. Effective stress transfer to the oriented whiskers resulted in outstanding enhancement in mechanical properties of the nanocomposites.